Targeting the Interaction Between Spike Protein and Nucleocapsid Protein for Suppression and Detection of Human Coronavirus OC43 - Kim, Jinsoo; Kim, Minyoung; Kim, Dongbum; Park, Sangkyu; Kang, Mijeong; Baek, Kyeongbin; Choi, Jun-Kyu; Maharjan, Sony; Akauliya, Madhav; Lee, Younghee; Kwon, Hyung-Joo (Frontiers in Immunology, 2022)
Human coronavirus OC43 (HCoV-OC43) is the coronavirus most associated with “common colds”, infections of the upper respiratory tract. Previously, we reported that direct interactions of nucleocapsid (N) protein and C-terminal domain of Spike protein (Spike CD) are essential for replication of SARS-CoV-2 and MERS-CoV. Thus, we developed a novel ELISA-based strategy targeting these specific interactions to detect SARS-CoV-2 and MERS-CoV. Here, we investigated whether the same principles apply to HCoV-OC43. We discovered that the S protein of HCoV-OC43 interacts with N protein and that cell penetrating Spike CD peptide inhibits virus protein expression and replication of HCoV-OC43. The interaction between HCoV-OC43 S and N proteins were recapitulated with a recombinant HCoV-OC43 Spike CD fusion protein and a recombinant HCoV-OC43 N fusion protein in vitro. By producing an anti-HCoV-OC43 N protein-specific monoclonal antibody, we established a virus detection system based on the interaction between recombinant Spike CD and N protein of HCoV-OC43. We suggest that the interaction between Spike CD and N protein is conserved in coronaviruses and therefore could be a target for therapeutics against both novel coronavirus and its variants.